Study on Effect of Aerodynamic Sound Hardening for Wear of Coated Carbide Metal Plates - V. K. Sheleg; A. N. Jigalov; D. D. Bogdan (Наука и техника, 2020)
To increase the durability of metal-cutting carbide plates operating during in harsh technological conditions with  impact  load, an aerodynamic sound  hardening  method  has  been developed  that can increase a life of  carbide  tools up to 3.7 times with a small added cost. The wear of plates hardened by the aerodynamic sound method, after 100 min of cutting, is 1.12–1.7 times less than their un-strengthened analogues. A coating on metal carbide plates does not have a prevailing value when a tool is working with impact loads. While working with impact loads viscosity of an internal plate structure occurs the greatest influence on increasing resistance. For metal-cutting carbide plates during interrupted cutting with significant impact loads, a method of aerodynamic sound hardening is more effective than a coating method, not only in terms of tool performance, but also in the cost of completion itself. Empirical dependences of wear on the rear surface of carbide plates hardened by a aerodynamic sound method and plates with PVD coatings have been obtained in the form of approximation by polynomials of the 5th and 2nd degrees, which are convenient to use in a production environment.  It has been revealed the higher carbide plate strength in bending leads to less influence of the method of aerodynamic sound hardening on the increase in wear resistance. So, taking into account the fact that for ВК8-base the ultimate bending strength is 1666 MPa, and for T5K10 it is 1421 MPa, wear reduction after hardening by the aerodynamic sound method for ВП3115-plates with ВК base is 11.5 %, while for ВП3225 – plates with ТК-base – 27.1 %.